Improving Educational Planning for Students With Severe Disabilities: An Evaluation of School-Based Professional Learning. Issue 1 (24th March 2015) - Stephenson, Jennifer; Carter, Mark
Abstract : The components of quality educational planning for students with moderate and severe intellectual disability are well established, but schools and special educators may not always achieve a desirable standard. This article reports on the change in quality of documentation related to individual planning and programming over a span of 4 years in a special school enrolling high-school-aged students with moderate to severe intellectual disability. The school implemented a program of professional learning, led by school staff, directed at improving planning and programming. There were significant changes in the quality of short-term goals and documentation of teaching programs. There was an increase in the quality of long-term goals but this did not reach significance. Instructional objectives were introduced in the final year of the study, and were not part of previous documentation. There was no evidence of implementation of formal monitoring procedures over the time span of the study. The difficulties observed and the changes as a result of the professional learning reflect those reported elsewhere in the literature, and demonstrate that a school commitment to improving program quality can have positive results.